2007
DOI: 10.1121/1.4781731
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates of talker-reported clear strategies

Abstract: When asked to speak clearly, talkers vary considerably in terms of the amount of intelligibility benefit achieved. The acoustic differences between clear and conversational speech also differ from talker to talker. The present study examined the extent to which clear speech acoustic modifications were consistent with talkers’ descriptions of the strategies they used in the clear speech condition during the recording of a large multitalker database [S. H. Ferguson, J. Acoust. Soc. Am. 116, 2365–2373 (2004)]. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For example, when conversing with a listener who has hearing limitations, a typical talker uses "clear speech." Such speech has been characterized by a slower speech rate, a wider range of fundamental frequency (fo), and a higher temporal modulation index than conversational speech (e.g., Picheny et al, 1985;Ferguson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when conversing with a listener who has hearing limitations, a typical talker uses "clear speech." Such speech has been characterized by a slower speech rate, a wider range of fundamental frequency (fo), and a higher temporal modulation index than conversational speech (e.g., Picheny et al, 1985;Ferguson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…That is, talkers may open their mouths wider in order to become louder, resulting in a lower tongue position for all vowels. Ferguson et al (2010) reported that on average, the present talkers spoke with 4 dB greater intensity in clear speech than conversational speech. The association between increased vocal intensity and increased F1 was explored by correlating unpublished speech intensity data from Ferguson (2002) with the average F1 change each talker produced in clear speech.…”
Section: Durationmentioning
confidence: 99%
“…Ferguson and Kewley-Port (2007) reported vowel acoustic data for 10 of the 41 talkers and reported a clear/conversational vowel duration ratio of 1.4. In addition, Ferguson et al (2010) measured speaking rate for all 41 talkers using sentence materials; the mean speaking rate in clear speech was 111 words per minute, significantly slower than the conversational speaking rate of 155 words per minute. Studies using other recorded materials have also reported longer vowel durations in clear speech.…”
Section: Durationmentioning
confidence: 99%
See 2 more Smart Citations